Elastic properties of amorphous carbon networks - Kelires, Pantelis C. (My University, 1994)
We calculated and analyzed for the first time the local atomic stress distributions and the elastic constants of realistic amorphous carbon networks. We found that there is always softening of the elastic constants of these isotropic systems, even in the case of nearly tetrahedral coordinations. The local stresses play a very important role in determining the hybridization of a site during the formation of the amorphous phase.
Keywords: Carbon; Hybridization